circSnx12 Is Involved in Ferroptosis During Heart Failure by Targeting miR-224-5p - Zheng, Haoyuan; Shi, Lin; Tong, Changci; Liu, Yunen; Hou, Mingxiao (Frontiers in Cardiovascular Medicine, 2021)
Circular RNA (circRNA), a member of non-coding RNAs, is able of tolerating exonuclease digestion. Iron ion homeostasis is essential for the body to maintain normal physiological functions. However, the relationship among circRNA, iron metabolism and heart failure remains largely unknown. This study aimed to explore the regulatory mechanism of circRNA and iron metabolism in heart failure. We obtain circRNA, miRNA and mRNA data from public databases and build a ceRNA network. The prediction results were verified in pressure-overload-induced heart failure mouse myocardial tissue samples using histopathological staining methods, iron and malondialdehyde (MDA) tests, quantitative real-time PCR (qRT-PCR), Western blot analysis and luciferase reporter assay. A total of 4 genes related to iron metabolism and oxidative stress were screened, and 7 circRNAs and 7 miRNAs that might interact with these genes were identified, and the ceRNA network was constructed. The results of qRT-PCR and Western blot experimental verification indicated that the expression patterns of FTH1, except for ATP6V1A, were similar with those predicted by bioinformatics analysis. Echocardiographic measurement showed that heart failure mice have lower fractional shortening and ejection fraction. In the myocardial tissue of mice with heart failure, we found that the myocardium displayed obvious fibrosis and the concentrations of iron and MDA were remarkably increased. In addition, circSnx12 could act as an endogenous sponge to adsorb miR-224-5p, and the 3'UTR region of FTH1 also contained miRNA binding sites. A circRNA-miRNA-mRNA regulatory network was successfully constructed by identifying differentially expressed genes related to iron metabolism. This new approach reveals potential circRNA targets for the treatment of heart failure.